INTRODUCTION TO SPECIAL ISSUE ON “FRONTIERS IN INDUSTRIAL MICROBIOLOGY AND BIOTECHNOLOGY 2020” - Baltz, Richard H.; Kao, Katy; Link, A. James; Marsili, Enrico; Reguera, Gemma; Shao, Zengyi; Vandamme, Erick J.; Jefries, Thomas W.; Gonzalez, Ramon (Journal of Industrial Microbiology & Biotechnology, 2020)
In 2014, the Journal of Industrial Microbiology and Biotechnology began publishing yearly Special Issues devoted to advances in industrial microbiology and biotechnology, with emphasis on individual core areas of the Society for Industrial Microbiology and Biotechnology (SIMB), our sponsoring society. In 2019, we expanded the special issues concept with the inaugural special issue on “Frontiers of Industrial Microbiology and Biotechnology 2019” to highlight the work of select authors who presented their work in any of the core areas of SIMB at the 2018 Annual Meeting of SIMB in Chicago, Illinois. That special issue was very successful, and we have repeated the process for the current Special Issue on “Frontiers in Industrial Microbiology and Biotechnology 2020”, covering select topics and authors who presented at the 2019 Annual Meeting of SIMB in Washington, DC.
Keywords: Type of access: Open Access; Industrial Microbiology; Biotechnology